2022
DOI: 10.52831/kjhs.1097901
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Hypoglycemic Confidence and Hypoglycemia Fear in Type 2 Diabetes Mellitus Patients

Abstract: Objective: This study aims to identify the relationship between hypoglycemic confidence and hypoglycemia fear in type 2 diabetes mellitus patients. Method: Designed as a descriptive and cross-sectional study, this research was conducted with 306 type 2 diabetes patients who visited the diabetes polyclinic to have an examination in period December 2021 and February 2022. The research data were collected by using the “Patient Identification Form”, the “Hypoglycemic Confidence Scale”, and the “Hypoglycemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…These findings are supported by prior research (Brown et al, 2019;Gül et al, 2021;Menekli & Şentürk, 2022;Sheikhi et al, 2020;Wu et al, 2023). In the current study, the hypoglycaemic confidence levels of patients with diabetes were moderate, and the hypoglycaemic confidence levels of patients with fear of experiencing hypoglycaemia were lower.…”
Section: Theme 3: Managing Hypoglycaemiasupporting
confidence: 90%
See 4 more Smart Citations
“…These findings are supported by prior research (Brown et al, 2019;Gül et al, 2021;Menekli & Şentürk, 2022;Sheikhi et al, 2020;Wu et al, 2023). In the current study, the hypoglycaemic confidence levels of patients with diabetes were moderate, and the hypoglycaemic confidence levels of patients with fear of experiencing hypoglycaemia were lower.…”
Section: Theme 3: Managing Hypoglycaemiasupporting
confidence: 90%
“…The patients reported that hypoglycaemia affected their physiological, psychological and social lives. The physiological symptoms reported by the patients were similar to those reported in the literature, which include trembling, cold sweating, feeling of hunger, exhaustion, dizziness, tingling and numbness have been reported in patients with hypoglycaemia (Gül et al, 2021;Menekli & Şentürk, 2022;Sherifali et al, 2018;TSEM, 2022). Our quantitative data show that approximately one in every three people has a fear of experiencing hypoglycaemia.…”
Section: Theme 3: Managing Hypoglycaemiasupporting
confidence: 81%
See 3 more Smart Citations